Liver Retransplantation in Patients With HIV‐1 Infection: An International Multicenter Cohort Study. Issue 2 (28th September 2015) - Agüero, F.; Rimola, A.; Stock, P.; Grossi, P.; Rockstroh, J. K.; Agarwal, K.; Garzoni, C.; Barcan, L. A.; Maltez, F.; Manzardo, C.; Mari, M.; Ragni, M. V.; et al.
Abstract : Liver retransplantation is performed in HIV‐infected patients, although its outcome is not well known. In an international cohort study (eight countries), 37 (6%; 32 coinfected with hepatitis C virus [HCV] and five with hepatitis B virus [HBV]) of 600 HIV‐infected patients who had undergone liver transplant were retransplanted. The main indications for retransplantation were vascular complications (35%), primary graft nonfunction (22%), rejection (19%), and HCV recurrence (13%). Overall, 19 patients (51%) died after retransplantation. Survival at 1, 3, and 5 years was 56%, 51%, and 51%, respectively. Among patients with HCV coinfection, HCV RNA replication status at retransplantation was the only significant prognostic factor. Patients with undetectable versus detectable HCV RNA had a survival probability of 80% versus 39% at 1 year and 80% versus 30% at 3 and 5 years (p = 0.025). Recurrence of hepatitis C was the main cause of death in the latter. Patients with HBV coinfection had survival of 80% at 1, 3, and 5 years after retransplantation. HIV infection was adequately controlled with antiretroviral therapy. In conclusion, liver retransplantation is an acceptable option for HIV‐infected patients with HBV or HCV coinfection but undetectable HCV RNA. Retransplantation in patients with HCV replication should be reassessed prospectively in the era of new direct antiviral agents.